The dynamic impact of higher education on youth employment opportunities and quality: an empirical analysis based on age-period-cohort models - Chen, Longyin; Guo, Jiru; Li, Wenting; Wang, Guyue (Frontiers in Sociology, 2025)
IntroductionEducation serves as a crucial mechanism influencing individuals’ labor income and social mobility in modern society, and whether one has attained higher education has become a key determinant in the allocation of competitive opportunities within the labor market. However, the impact of this determinant on youth employment is inherently dynamic, shaped both by micro-level life course trajectories and by macro-level processes of social transformation.MethodsDrawing on eight waves of data from the China Social Survey (CSS) covering 2006–2021, this study applies a Hierarchical Age–Period–Cohort Cross-Classified Random Effects Model (HAPC-CCREM) to assess how higher education influences young people’s employment outcomes in the labor market. The analysis considers two dimensions of employment performance—opportunities and quality—while also mapping dynamic trends across age, period, and cohort.ResultsHigher education has a significant impact on all three dimensions of youth employment. Age: For higher-education youth, both employment opportunities and quality follow an inverted U-shaped curve, whereas for non-higher-education youth both indicators increase gradually. Period: Employment opportunities for both groups have undergone cyclical declines since 2006, but the decrease has been less steep for higher-education graduates, who have consistently outperformed their non-higher-education peers. In terms of employment quality, higher-education graduates show a fluctuating upward trend, while non-graduates maintain relatively stable levels. Cohort: Among higher-education cohorts, the effect on both employment opportunities and quality displays a “gradual rise–sharp decline” trajectory, whereas among non-higher-education cohorts, the pattern is one of “moderate fluctuations–mild improvement.”ConclusionWhile higher education significantly enhances youth employment opportunities and job quality, its returns decline in the later stages across all three temporal dimensions and are increasingly constrained by credential inflation and labor market structural transformations. This underscores the urgency of aligning higher education with the evolving labor market and implementing targeted employment policies.